1998
DOI: 10.1089/dna.1998.17.869
|View full text |Cite
|
Sign up to set email alerts
|

Rat Somatostatin Receptor Subtype 4 Can Be Made Sensitive to Agonist-Induced Internalization by Mutation of a Single Threonine (Residue 331)

Abstract: A sequence motif of 20 amino acid residues within the C-terminal portion of the rat somatostatin receptor subtype 4 (SSTR4) has been shown to prevent rapid agonist-dependent receptor internalization in transfected human embryonic kidney (HEK) cells. Molecular dissection of this motif by biochemical ligand-binding assays revealed that the block was released by mutating a single residue (threonine 331) to an alanine. These data are in line with confocal microscopic analysis of cultured primary neurons microinjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
33
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 23 publications
1
33
0
Order By: Relevance
“…onine residues occupying four of five positions in its carboxylterminal tail (13). In addition, we demonstrate that the sst 4 receptor was resistant to agonist-induced phosphorylation and ␤-arrestin-dependent trafficking even in the presence of GRK2.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…onine residues occupying four of five positions in its carboxylterminal tail (13). In addition, we demonstrate that the sst 4 receptor was resistant to agonist-induced phosphorylation and ␤-arrestin-dependent trafficking even in the presence of GRK2.…”
Section: Discussionmentioning
confidence: 73%
“…These results imply either peculiar mechanisms of receptor desensitization or resistance to desensitization. In fact, it has previously been shown that the rat sst 4 receptor fails to internalize after agonist activation (13). Consistent with the previous findings, we show that sst 4 did not undergo any detectable phosphorylation after agonist activation despite the presence of a number of potential phosphate acceptor sites including a cluster of thre- 3 was used to examine colocalization between a 30-min agonist pulse of antibody-labeled receptors (red) followed by a 20-min chase with transferrin (green) in the absence of SS-14 as described under "Experimental Procedures."…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the changes in the CA1 region were due to the sst 1/4 receptors. The sst 1 and sst 4 subtypes are found in the hippocampus but unlike the sst 2 subtype were shown to have poor internalization yields (Nouel et al, 1997;Kreienkamp et al, 1998;Stroh et al, 2000). In a recent publication new evidence is provided showing that sst 1 mediates agonist-induced endocytosis, recycling and reendocytosis of its cognate ligand (Roosterman et al, 2007) 4 alone, something that we cannot examine due to lack of specific radioligands.…”
Section: Discussionmentioning
confidence: 84%